WAYS TO INCREASE INVESTMENT POTENTIAL IN SAMARKAND REGION (Academicia Globe: Inderscience Research, 2021)
The article highlights the issues related to the regional specifics of investment activities in the Samarkand region. Formation and improvement of investment attraction mechanisms for the effective conduct of investment activities in the region, presentation of promising project proposals for a business wishing to invest, development and systematic implementation of high-quality projects, mutually beneficial cooperation with foreign partners, scientifically based proposals and recommendations. to create favorable conditions for the activities of investors, to attract investments.